2017
DOI: 10.3390/ijms19010002
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mechanisms of Electroacupuncture-Induced Analgesia through RNA Sequencing of the Periaqueductal Gray

Abstract: Electroacupuncture (EA) can relieve various pains. However, its mechanism in terms of the transcriptome is still not well-known. To explore the full profile of EA-induced molecular modification in the central nerve system, three twins of goats were selected for a match-paired experiment: EA stimulation (60 Hz, 30 min) and none-EA (control). Goats in the EA group showed an increased (p < 0.05) nociceptive threshold compared with the control goats. Experimental goats were sacrificed at 4 h of the experiment, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 94 publications
(126 reference statements)
1
9
0
Order By: Relevance
“…ATP2B2, a magnesium-dependent enzyme that catalyzes the hydrolysis of ATP coupled with calcium transport, is a known constituent of the CNS myelin proteome [ 35 ] but its function in OPCs remains to be investigated. PCSK1N, a neuropeptide [ 132 ], is a proliferation-related molecule [ 133 ]. There is no evidence that directly focuses on the role of PCSK1N in OPC function or maintenance; however, it has been reported that, in the mouse insulinoma 6 (MIN6) cell line, Pax6 can directly downregulate Pcsk1n expression [ 134 ].…”
Section: Data Descriptionmentioning
confidence: 99%
“…ATP2B2, a magnesium-dependent enzyme that catalyzes the hydrolysis of ATP coupled with calcium transport, is a known constituent of the CNS myelin proteome [ 35 ] but its function in OPCs remains to be investigated. PCSK1N, a neuropeptide [ 132 ], is a proliferation-related molecule [ 133 ]. There is no evidence that directly focuses on the role of PCSK1N in OPC function or maintenance; however, it has been reported that, in the mouse insulinoma 6 (MIN6) cell line, Pax6 can directly downregulate Pcsk1n expression [ 134 ].…”
Section: Data Descriptionmentioning
confidence: 99%
“…As a vital integrative center in antinociceptive effect of EA, the PAG receives not only the ascending nociceptive input but also the descending anti-nociceptive signals from the higher central regions. The RNA sequencing performed in goat PAG showed that five neuropeptides genes, glutamatergic synapse, GABAergic synapse, MAPK, ribosome and ubiquitin-proteasome pathway may be implicated in EA-induced analgesia (Hu et al, 2017).…”
Section: Other Transmitters Related To Ea-induced Analgesiamentioning
confidence: 99%
“…Numerous studies confirmed that EOPs in the CNS participate in EA-induced analgesia regulation (Sun and Han, 1989; Staff, 2014; Cui and Ding, 2016; Hu et al, 2018). However, EOP expression patterns in some nuclei or areas in the development and recovery of EAT have been rarely reported.…”
Section: Discussionmentioning
confidence: 92%